Targeted therapyPart II. Clinical use of tyrosine kinase inhibitors – monoclonal antibodies - Skoczek, Marta; Grela-Wojewoda, Aleksandra; Rolski, Janusz (Contemporary Oncology/Współczesna Onkologia, 2008)
Receptor tyrosine kinases are transmembrane proteins involved in signal transduction. They propagate growth factor signals from the cell surface to the cell interior and control such critical processes as growth of the cell, differentiation, angiogenesis and inhibition of apoptosis. In malignancies these signaling pathways are often exploited to optimize tumour growth and metastasis. One such family of receptor tyrosine kinases is epidermal growth factor receptor (EGFR) tyro- sine kinase. These receptors are overexpressed in a wide variety of epithelial cancers and have been implicated in tumour aggressiveness. Thus, targeting the EGFR tyrosine kinase has attracted considerable attention. This review will summarize current preclinical and clinical knowledge of such EGFR inhibitors as monoclonal antibodies (small molecule inhibitors will be presented in the next article). The pharmacological properties and anticancer activities of these inhibitors are discussed in this article. They have a favorable safety profile and can be easily combined with other forms of anticancer therapy like chemotherapy and radiation therapy. The use of these targeted therapies is not without limitations such as the development of resistance and the lack of tumour response in the general population. The availability of the newer inhibitors and improved patient selection will help to overcome these problems in the future.